The Sultanate of Murad II (1421-1451) of the Ottoman Empire - Mohd Isa, Ammalina Dalillah; Omer, Spahic; Fathil, Fauziah (International Journal of Advanced Research (IJAR), 2022)
Murad II was the sixth Ottoman sultan reigning from 1421 until 1451. Although his nature of ruling was acclaimed by the Ottoman historians and travelers and chroniclers of his time, research on the sultanate of Murad II was understudied. Franz Babinger, a well-known Ottoman classical history scholar stated that, “No book has been devoted to the life and sultanate of Mehmed’s father and predecessor, Murad II.” Thus, this study aims to explore the sultanate of Murad II in the Ottoman Empire from 1421-1451. This study employed a qualitative method through historical study and content analysis method. The method of data collection for this study was document research by analyzing textual and visual data from primary and secondary sources. The data were analysed through hermeneutic and descriptive methods. This study discovered that throughout Murad II rule, numerous crises emerged in his realm right after his enthronement and some of them threatened the sustainability of the Ottoman Empire. Nevertheless, he navigated the threats and crises adequately but effectively. As a result, he was able to consolidate and fully recover the Ottoman Empire after the impact of the Battle of Ankara. His nature of rule with justice, moderate tolerance and aggressiveness made him a great ruler, enjoyed by the members of his courts, pleased by his subjects, and admired by his opponents.